Charging Strategies Influence on DC-DC Converter and Li-Ion Battery Performance - Tahir, Muhammad Usman; Chakraborty, Sajib; Akboy, Erdem; Sangwongwanich, Ariya; Stroe, Daniel Joan; Hegazy, Omar; Blaabjerg, Frede (IEEE, 2024)
The increasing demand for Lithium-ion batteries (LIBs) in electric vehicles (EVs) highlights the necessity for new efficient charging strategies to improve performance and extend battery lifetime. This paper investigates the effect of constant current (CC), constant power (CP), and five-stage constant current (5SCC) charging techniques on the LIB pack and also DC-DC converter performance parameters. Critical parameters such as efficiency, temperature rise, charging time, and capacity are evaluated experimentally. The results indicate that the 5SCC charging strategy achieves approximately 28% higher input capacity, with a trade-off of a 5 degrees C increase in temperature compared to CC charging. In addition, CP charging exhibits superior efficiency, 1.58% more efficient than CC charging. Thus, the 5SCC strategy is especially beneficial for applications prioritizing higher charged input capacity, while the CP strategy is valuable for those focusing on charging energy efficiency. This work can support the charge point operators (CPOs) in determining the optimal charging strategy corresponding to the performance target and application needs.
Keywords: Thermal Performance; Fast Charging Strategies; LIB Pack; DC-DC Converter; Converter Efficiency; Energy & Fuels; Engineering